Outcome in 212 anti‐Ro/SSA‐positive pregnancies and population‐based incidence of congenital heart block. (26th October 2015) - Skog, Amanda; Lagnefeldt, Linda; Conner, Peter; Wahren‐Herlenius, Marie; Sonesson, Sven‐Erik
Abstract: Introduction: We investigated the effects of maternal autoimmune disease and fetal congenital heart block (CHB) on pregnancy outcomes in anti‐Ro/SSA‐positive women and assessed the population‐based incidence of isolated CHB. Material and methods: One hundred and ninety nine anti‐Ro/SSA‐positive pregnancies were prospectively followed at our center (2000–2013). Seven fetuses developed atrioventricular block (AVB) II–III. In this period, another 13 anti‐Ro/SSA‐positive pregnancies were referred for fetal bradycardia, subsequently diagnosed with AVB II–III. Cesarean section rates, gestational age, body measurements at birth, and the incidence of CHB in these 212 pregnancies were analyzed in relation to fetal atrioventricular conduction and maternal diagnosis and compared with data from the Medical Birth Registry on 352 104 pregnancies in the Stockholm County. Results: The prevalence of maternal systemic lupus erythematosus (SLE) and primary Sjögren's syndrome and the outcomes at birth were similar in normal conduction and AVB I cases. Only 1/20 AVB II–III cases (0/7 in the surveillance group) had a mother diagnosed with SLE, compared with 73/192 in cases with normal conduction or AVB I. Excluding cases with AVB II–III, SLE mothers more frequently delivered by cesarean section (31% vs. 20%, p < 0.05) and had a higher incidence of preterm birth (13% vs. 5.8%, p < 0.05) than the county population. Both SLE and primary Sjögren's syndrome mothers had a fourfold greater rate of growth‐retarded babies (10.11% vs. 2.2%, p < 0.001). The incidence of autoantibody‐related AVB II–III in Stockholm County was 1/23 300. Conclusion: This study of CHB provides new information on the incidence of CHB and outcome of pregnancy in anti‐Ro/SSA‐positive women, which has clinical relevance when counseling rheumatic patients considering pregnancy.